Hukum Perkawinan Islam di Bawah Tekanan Modernitas: Studi Historis dan Yuridis Atas Reformasi di Mesir, Turki, Pakistan, dan Irak: Penelitian - Fauzi Dahrial; Elimartati; Ramza Fatria Maulana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the dynamics of Islamic family law reform in four Muslim countries: Egypt, Turkey, Pakistan, and Iraq with a historical and juridical approach. Islamic family law has a unique epistemological position because it is seen as part of a permanent and transcendent divine law. However, in practice, this law has undergone a significant reform process, especially under the pressure of modernity, secularization, and demands for social justice and gender equality. This study uses a qualitative method through library research with a descriptive-analytical and comparative approach, and utilizes primary and secondary legal sources from the four countries. The results of the study show that Egypt carried out family law reform through cross-school codification and the maqashid al-shariah approach, Turkey carried out full secularization by adopting the Swiss Civil Code, Pakistan implemented reform through the Muslim Family Laws Ordinance 1961 with procedural strengthening of women's rights, while Iraq displayed a pluralistic approach that combined elements of the Sunni and Shia schools of thought in the Personal Status Law of 1959. Although each country has a different model and context, all of them show a tendency to adapt fiqh law to contemporary social needs.